Russian National Consensus Statement on gestational diabetes: diagnostics, treatment and postnatal care - Ivan Ivanovich Dedov; Vladislav Ivanovich Krasnopol'skiy; Gennadiy Tikhonovich Sukhikh (Сахарный диабет)
Current document presents the expert consensus of Russian Association of Endocrinologists and Russian Society of Obstetrician- Gynecologists on diagnostic criteria of gestational diabetes and other glycemic disorders of pregnancy. The consensus is based on analysis of HAPO (Hyperglycemia and Adverse Pregnancy Outcomes Study) - a major multinational study, that included more than 23000 patients. Project of current consensus was repeatedly discussed during meetings of the research group and publicly addressed at 6th Pan-Russian Congress of Endocrinology with international participation ?Modern Endocrine Technologies?, as well as Pan-Russian Educational Interscience Conference ?Complicated Pregnancy and Preterm Birth?.